Mengungkap Hubungan: Employee Engagement dan Produktivitas Kerja di PT PLN Unit Layanan Pelanggan Mande Cianjur - Jaelani, Dede (Portofolio: Jurnal Ekonomi, Bisnis, Manajemen, dan Akuntansi, 2025)
Work productivity is an important indicator of a country's competitiveness on a global scale, reflecting the efficiency of the workforce in generating output. However, worker productivity in Indonesia remains low, only about 20% of that in developed countries such as the United States and Singapore (The Conference Board, 2023). This low productivity is influenced by factors such as technology, infrastructure, and the level of employee engagement (World Bank, 2022).The type of research in this study is quantitative, with a descriptive and associative research design that illustrates the conditions and relationships between independent and dependent variables. The results from the research conducted at PT PLN Customer Service Unit Mande Cianjur indicate that employee engagement and work productivity are categorized as high, with a very strong relationship (r = 0.970, p = 0.000) and significant influence (β = 2.039). High employee engagement contributes to increased work productivity, reflecting better efficiency, quality, and discipline. These findings are in line with previous research that emphasizes that employee engagement is a key factor in enhancing productivity, thus companies need to continuously encourage employee involvement to maintain and improve organizational performance.